DINAMIKA SIKAP DAN RESPONS MASYARAKAT MUSLIM TERHADAP PENERAPAN SHAF BERJARAK DI KABUPATEN GOWA - Muslim, Asrul; Irham, Muhammad (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2023)
This research aims to elaborate on the Muslim community's response to implementing spaced prayer rows in mosques during the Covid-19 pandemic as well as the factors causing this resistance. This research is qualitative with a phenomenological and sociological approach. Primary data consists of regular congregation members and administrators of several mosques in the Gowa Regency. The data collection methods used were observation, interviews, and documentation. Data processing and analysis techniques are carried out through data reduction, data display, and drawing conclusions. The research results show that community resistance to the implementation of distance rows is due to two main factors, namely cognitive factors and depressive policies. Cognitive factors show that people do not understand the law properly regarding emergency conditions in the implementation of worship. Meanwhile, repressive policies are more about approaches that do not accommodate the cultural situation of society, including cognitive factors. This has an impact on the society’s disobedience to government calls and regulations as well as ulama fatwas as a form of resistance to those rules.